Unusual presentation of Cerebral lupus: A case report of Parkinsonism in Cerebral lupus - Chang, Chee Keong; Malehah Mohd Noh; Liew, Constance Sat Lin; Alvin Oliver Payus (S. Karger AG, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multisystem involvement that follows a relapsing and remitting course. It is characterized by an immune-mediated response to own body defense mechanism and mistakenly attacked healthy cells of the skin, joints, kidneys, blood cells, and nervous system. Cerebral lupus refers to a constellation of neurological and/or behavioral clinical syndromes in patients with SLE. The spectrum of presentation can vary widely ranging from mild symptoms such as headaches, slight cognitive dysfunction, and mood disorders to more serious conditions like seizures, stroke, or coma. This case report is about a case of cerebral lupus manifested with symptoms of Parkinsonism. The purpose of this case report is to share an uncommon occurrence of cerebral lupus which manifested as Parkinsonism and to highlight the importance of early diagnosis of the condition which is potentially reversibility with prompt.